2016
DOI: 10.12659/ajcr.899022
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt Lymphoma Presenting as an Intracardiac Mass: Case Report and Review of Literature

Abstract: Patient: Male, 27Final Diagnosis: Burkitt lymphoma with intracardiac massSymptoms: Dizziness • fatigue • palpitations • weight lossMedication: —Clinical Procedure: Catheter-directed thrombolytic therapy with intracardiac infusion of alteplaseSpecialty: HematologyObjective:Rare diseaseBackground:Non-neoplastic causes such as infections and thrombi account for most intracardiac masses. Primary tumors such as myxomas and metastasis from breast cancer, lung cancer, or melanomas account for many of the remaining ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Chan et al, did a review of the literature and found only 22 cases reported in the English literature including their case. Only 7 of these were in patients with confirmed negative HIV status [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chan et al, did a review of the literature and found only 22 cases reported in the English literature including their case. Only 7 of these were in patients with confirmed negative HIV status [4].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is high as reported back in 2008 by Chan et al In their review of the literature almost 50% of the 22 cases and with the longest surviving patient reported to be alive at 36 months after the diagnosis [4]. With new chemotherapy regimens, better imaging modalities, and multidisciplinary management of these patients, early diagnosis and more effective treatment prevent these patients from getting locally advanced cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to rarity of its occurrence accurate epidemiology and etiology of PHBL are not established. In our patient, BL was associated with acquired immunodeficiency, due to chronic immunosuppressive therapy for KTx [ 4 ], but also with Epstein-Barr viremia [ 5 ]. Epstein-Barr virus, a member of the human herpes virus family, is a linear, double-stranded DNA virus that was initially isolated from a cultured BL cell line by Epstein et al in 1964.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic symptoms are seen less than 25% of patients. Rarely cardiac and pulmonary involvement may be seen [3]. Patients can present with cough, dyspnea and chest pain.…”
Section: Introductionmentioning
confidence: 99%